A molecular structure-informed viscoelastic constitutive model for natural rubber materials. (22nd November 2021) - Jung, Jiwon; Park, Chanwook; Ryu, Myung Shin; Yun, Gun Jin
Abstract: This paper presents a molecular structure-informed viscoelastic constitutive equation that adopts the Doi–Edward's tube model with coarse-grained molecular dynamics simulation and primitive path analysis. Since this model contains polymer physics-related parameters directly obtained from molecular simulations, it can reflect molecular information in predictions of the viscoelastic behavior of elastomers, unlike other empirical models. The proposed incremental formulations and constitutive stiffness matrix were implemented into implicit finite element analysis codes as a user-supplied material model and viscoelastic properties (storage, loss modulus, and tan δ ) were calculated from the constitutive equation. While obtaining polymer dynamics parameter of the molecular system, a relationship between self-diffusivity coefficient ( D c ) and the polymerization degree of the polymer was confirmed. Furthermore, a series of parametric studies showed that increase of the primitive path length ( L ) and decrease of D c have led to the strengthening of moduli and decrease of tan δ peak. Moreover, under the same condition, the shift of tan δ peak to low-frequency domain was observed, which implies a decline in free volume in the molecular system and an increase in the glass transition temperature.